Three-Staged Stereotactic Radiotherapy Without Whole Brain Irradiation for Large Metastatic Brain Tumors - Higuchi, Yoshinori; Serizawa, Toru; Nagano, Osamu; Matsuda, Shinji; Ono, Junichi; Sato, Makoto; Iwadate, Yasuo; Saeki, Naokatsu (International journal of radiation oncology, biology, physics, 2009)
To evaluate the efficacy and toxicity of staged stereotactic radiotherapy with a 2-week interfraction interval for unresectable brain metastases more than 10 cm 3 in volume. Subjects included 43 patients (24 men and 19 women), ranging in age from 41 to 84 years, who had large brain metastases (> 10 cc in volume). Primary tumors were in the colon in 14 patients, lung in 12, breast in 11, and other in 6. The peripheral dose was 10 Gy in three fractions. The interval between fractions was 2 weeks. The mean tumor volume before treatment was 17.6 ± 6.3 cm 3 (mean ± SD). Mean follow-up interval was 7.8 months. The local tumor control rate, as well as overall, neurological, and qualitative survivals, were calculated using the Kaplan-Meier method. At the time of the second and third fractions, mean tumor volumes were 14.3 ± 6.5 (18.8% reduction) and 10.6 ± 6.1 cm 3 (39.8% reduction), respectively, showing significant reductions. The median overall survival period was 8.8 months. Neurological and qualitative survivals at 12 months were 81.8% and 76.2%, respectively. Local tumor control rates were 89.8% and 75.9% at 6 and 12 months, respectively. Tumor recurrence-free and symptomatic edema-free rates at 12 months were 80.7% and 84.4%, respectively. The 2-week interval allowed significant reduction of the treatment volume. Our results suggest staged stereotactic radiotherapy using our protocol to be a possible alternative for treating large brain metastases.